1982
DOI: 10.1007/bf02323363
|View full text |Cite
|
Sign up to set email alerts
|

Values of UV- and global radiation in the northern Alps

Abstract: Radiation values of the solar spectral range are represented over a period of 5 years at three neighboring, vertically graduated stations at 740, 1780, and 1964 m a.s.1, in the mountains (Bavarian Alps). Additional to global radiation the UV-radiation in the range from 310 to 340 nm and the daily sunshine duration are recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…Fig. 2 shows monthly mean activity concentrations for 21 "Pb from Fribourg, Switzerland [37] and Neuherberg, Germany [36] for the time period 1973-1981. Both locations are on the northern side of the Alps at a distance of 360 km.…”
Section: Lead-210mentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 2 shows monthly mean activity concentrations for 21 "Pb from Fribourg, Switzerland [37] and Neuherberg, Germany [36] for the time period 1973-1981. Both locations are on the northern side of the Alps at a distance of 360 km.…”
Section: Lead-210mentioning
confidence: 99%
“…Especially during the summer period convective vertical transport from nearby valleys cause an increase of the local activity concentrations ( Fig. 1) [15,21], 222 Rn activity concentrations reach values of about 10 to 100 mBq/m 3 (STP) in the tropopause and lower stratosphere [20,22,23]. However, it was found that advective transport of radon-rich air from the boundary layer can reach the upper troposphere [24] or even the stratosphere [22] nuclide 2U) Pb (T U1 = 22 years).…”
mentioning
confidence: 99%
“…23,24 In the cloudier, humid weather of the Alps UV radiation increases 24% per thousand meters or 7% per thousand feet. 20 One study found UV increased up to 19% for each thousand meters or about 5% for each thousand feet 28 and another reported that UV increased 10% per vertical kilometer. 27 Regardless of the exact increase in UV studies all show that altitude, clear air, and reflected UV from snow make the alpine environment dangerous.…”
mentioning
confidence: 99%
“…In temperate latitudes, UV peaks on the summer solstice and is lowest at the winter solstice, 19 though indirect, diffuse UV can be high in winter. 17,20,15 UV peaks at solar noon and is highest at low latitudes. 14 Likewise, solar radiation is considerably greater at high elevations rather than sea level.…”
mentioning
confidence: 99%
See 1 more Smart Citation